Effect of creatine supplementation on the airways of youth elite soccer players - Simpson, A. J.; Horne, S.; Sharp, P.; Sharps, R.; Kippelen, P. (Medicine & Science in Sports & Exercise, 2019)
Introduction Owing to its well-established ergogenic potential, creatine is a highly popular food supplement in sports. As an oral supplement, creatine is considered safe and ethical. However, no data exist on the safety of creatine on lung function in athletes. The aim of this project was to evaluate the effects of a standard course of creatine on the airways of youth elite athletes. Methods Nineteen elite soccer players, 16-21 yr old, completed a stratified, randomized, double-blind, placebo-controlled, parallel-group trial. The creatine group ( n= 9) ingested 0.3 g/kg·d of creatine monohydrate (CM) for 1 wk (loading phase) and 5 g/d for 7 wk (maintenance phase), and the placebo group ( n= 10) received the same dosages of maltodextrin. Airway inflammation (assessed by exhaled nitric oxide, F ENO) and airway responsiveness (to dry air hyperpnoea) were measured pre- and postsupplementation. Results Mild, unfavorable changes in F ENO were noticed by trend over the supplementation period in the CM group only ( P= 0.056 for interaction, Eta2= 0.199), with a mean group change of 9 ± 13 ppb in the CM group versus - 5 ± 16 ppb in the placebo group ( P= 0.056, d= 0.695). Further, the maximum fall in forced expiratory volume in 1 s after dry air hyperpnoea was larger by trend postsupplementation in the CM group compared with the placebo group: 9.7% ± 7.5% vs 4.4% ± 1.4%, respectively ( P= 0.070, d= 0.975). These adverse effects were more pronounced when atopic players only ( n= 15) were considered. Conclusion On the basis of the observed trends and medium to large effect sizes, we cannot exclude that creatine supplementation has an adverse effect on the airways of elite athletes, particularly in those with allergic sensitization. Further safety profiling of the ergogenic food supplement is warranted.